The effects of Citrus aurantium aroma on anxiety and fatigue in patients with acute myocardial infarction: A two-center, randomized, controlled trial - Shirzadegan, Razieh; Gholami, Mohammad; Hasanvand, Shirin; Beiranvand, Afsaneh (Journal of herbal medicine, 2020)
•Anxiety is a multifactorial phenomenon in hospitalized patients with acute myocardial infarction.•Fatigue is the most common prodromal symptom of myocardial infarction.•Aromatherapy with Citrus aurantium as a sedative and soporific herb has been practiced in Iranian traditional medicine.•Aromatic oils can inhibit the γ-aminobutyric acid pathways and suppress the neurotransmitters, which makes them a good alternative for alleviating fatigue.•Aromatherapy with the essential oil of Citrus aurantium is an easy, inexpensive and harmless method that reduces anxiety and fatigue among patients with acute myocardial infarction. Anxiety and fatigue affect the clinical course and quality of life in patients with Acute Myocardial Infarction (AMI). Complementary therapies are recommended for managing these symptoms. The present study was conducted to evaluate the effects of Citrus aurantium aroma on anxiety and fatigue in patients with AMI admitted to coronary care units. In this triple-blind, randomized, controlled, clinical trial, 80 patients with AMI were allocated to a Citrus aurantium group and a placebo group (n = 40 per group) through stratified randomized blocks. From their second day of hospitalization and for two consecutive days, the subjects in the experimental and control groups inhaled three drops of Citrus aurantium essential oil or the placebo using absorbable patches connected to the inside of oxygen masks for 20 min. Anxiety and fatigue were measured in the patients using the Spielberger State-Trait Anxiety Inventory (STAI) and the Multidimensional Fatigue Inventory (MFI-20) 30 min before and 15 and 30 min after the interventions. There was a statistically significant difference between the Citrus aurantium and placebo groups concerning the mean changes in their anxiety and fatigue scores (P < 0.001Citrus aurantium essential oil reduced anxiety and fatigue on all the four measurement occasions after the intervention compared to before. Aromatherapy with Citrus aurantium can be used as part of holistic care for managing the symptoms of AMI by nurses.